A Survey of Safety Recommendations for All-Terrain Vehicle Dealers and Track Owners in Kansas - Martin, Morgan J.; Morton, Rychael; Rau, Shawn; Nyberg, Sue; Berg, Gina M. (Kansas Journal of Medicine, 2019)
Introduction. All-terrain vehicles (ATVs) are associated with injury, mortality, and healthcare costs. ATV related injuries are less severe when consistent safety practices are followed, however, ATV safety regulations are varied among states. This study sought to survey Kansas ATV dealers and track owners to determine safety promotion practices. Methods. A cross-sectional telephone survey was conducted of Kansas ATV dealers and tracks. Survey questions included promotion and sale of safety equipment, provision of ATV safety information, and respondent characteristics. Results. Of those contacted, 32% of dealers and 31% of tracks responded to the survey. Most ATV dealers sell safety gear (70% - 100%) and all recommend safety gear to buyers and riders. All ATV tracks reported requiring helmets (100%) but were varied regarding other forms of safety gear. The majority of ATV dealers (77%) recommended safety courses, but only 31% of dealers and 40% of tracks offered courses. Eighty percent of ATV tracks and 52% of dealers felt they had a professional responsibility to educate riders/owners on safety. Conclusions. Safety promotion by ATV dealers in Kansas consistently was recommended, but often limited to the sales of safety gear (helmets and gloves) or the provision of manufacturer provided safety materials. Further, ATV dealers reported rarely offering skills tests or safety courses to buyers. In Kansas, safety promotion at the point of sale or track level could be improved to increase public awareness of ATV safety practices. KS J Med 2017;10(4):76-78.